Understanding the Importance of Email Etiquette and Addressing Email Communication Challenges Among BTVI Students - Nathir Ghafar, Zanyar (RADINKA JAYA UTAMA PUBLISHER, 2024)
Email serves as a communication channel for students in higher educational institutions to interact with teachers on course materials, assignments, and impending tests and seek guidance on personal or academic concerns. The present research examines student-instructor email communication, explicitly identifying the problematic elements in students' emails that hinder effective communication. The study examines a sample of 50 email communications composed and sent by first-year students to their instructors at Bright Technical and Vocational Institute (BTVI) in Kurdistan. Textual analysis is a valuable method for investigating research inquiries across several disciplines. The study findings demonstrated that informal aspects of student email exchanges include the usage of slang, overuse of capitalization, unconventional spelling, symbols, and emoticons. Lack of adherence to email etiquette norms and grammatical errors. These elements indicate a need for more understanding of formality, professionalism, and the decorum expected in a university atmosphere. Thus, it is advisable to implement pedagogical intervention to develop the necessary abilities for composing and comprehending emails. Providing education and assistance on the protocols and norms of email communication may enhance students' capacity to effectively and professionally interact via email in (BTVI), hence fostering good practices and increasing future employment prospects.